ANALISIS EFEKTIVITAS METODE KONSUMSI DALAM PERENCANAAN KEBUTUHAN OBAT DI PUSKESMAS X KABUPATEN X TAHUN 2023 - Amelia Nindya Putri (2023)
The planning of drug needs carried out at the Puskesmas X is considered inappropriate because stockouts and stagnants are still found. The purpose of this study was to analyze the effectiveness of the consumption method in planning drug needs at the Puskesmas X. This study used a descriptive research design with a qualitative approach through in-depth interviews and document review. The research informants consisted of 3 people (Head of Puskesmas, Person in Charge of Pharmaceutical Installation, and Pharmaceutical Installation Staff). Descriptive data analysis to determine effective planning methods using the level of drug availability. The results showed that drug planning at Puskesmas X is in accordance with existing regulations, but in its implementation it is still not optimal because the calculation is not in accordance with existing theory, besides that the consumption method is said to be more effective than the method used previously because it is able to increase drug availability and minimize shortages and excess drugs. Puskesmas X is expected to calculate drug needs in accordance with the rules in Permenkes No. 74 of 2016, make pharmacist requests to the local office, and improve coordination between staff at the health center.